PENGEMBANGAN MASYARAKAT LINGKAR TAMBANG DALAM PENGUSAHAAN PERTAMBANGAN - Christine J.J. Goni; Michael Barama; Olga Anatje Pangkerego (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Indonesia is a country rich in mining resources. Mining resources include gold, silver, copper, oil and gas, coal and others. There are a large number of companies operating in the mining sector and investing in the mining sector. Mining operations in Indonesia have caused a lot of controversy. On the one hand, mining operations benefit the government and entrepreneurs, but on the other hand, they sacrifice the environment, causing many problems for the lives of people around the mine. The aim of this research is to analyze the legal aspects related to mining operations and analyze the legal regulations regarding the development of mining communities and the forms of development of mining communities carried out by PT. MSM. The first research method used is a normative juridical research method to find the truth from a normative perspective through a legislative approach from Laws, Presidential Decrees, Presidential Decrees, Ministerial Regulations and concepts regarding the development of mining communities in mining operations. The second research method is empirical juridical research to discover forms of community development around the mine through direct interviews with related parties. The research results related to mining business regulations are based on Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia that states that the Earth, Water and Wealth contained therein are controlled by the state and used as much as possible for the prosperity of the people. Other regulations are contained in Law No. 4 of 2009 concerning Mineral and Coal Mining which has been amended with the enactment of Law No. 3 of 2020. Regulations related to the development and empowerment of communities around mines are also regulated in Minerba Law No. 3 of 2020 and related to CSR, it is regulated in Law No. 40 of 2007 concerning Limited Liability Companies which requires PT business entities to carry out CSR programs. Furthermore, in Minister of Energy and Mineral Resources Regulation No. 41 of 2016 regulates Community Development and Empowerment in Mineral and Coal Mining Business Activities. The existence of PT MSM as a company that carries out gold mining business activities in North Minahasa Regency, North Sulawesi Province has contributed to the development and empowerment of communities around the mine through CSR programs in the fields of infrastructure, education, use of labor and the environmental sector.